EFEKTIVITAS PENERAPAN PPT INTERAKTIF DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA PEMBELAJARAN MATEMATIKA PEMBAGIAN FASE B - Marcellino Tyas Endy Kesuma Putra; Aditya Kristrifena (STKIP Subang, 2024)
The purpose of conducting this meta-analysis is to investigate the effectiveness of utilizing Interactive PowerPoint as a learning media in enhancing problem-solving skills in elementary school mathematics education. The research methodology employed is qualitative, coupled with a meta-analysis of previously researched and still relevant journal sources. The results of this meta-analysis indicate that the use of Interactive PowerPoint media can enhance students' engagement and interest in learning materials, as well as contribute to the improvement of students' mathematical problem-solving abilities.